2018
DOI: 10.1186/s12898-018-0190-z
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and limitations of three-dimensional printing technology for ecological research

Abstract: BackgroundEcological research often involves sampling and manipulating non-model organisms that reside in heterogeneous environments. As such, ecologists often adapt techniques and ideas from industry and other scientific fields to design and build equipment, tools, and experimental contraptions custom-made for the ecological systems under study. Three-dimensional (3D) printing provides a way to rapidly produce identical and novel objects that could be used in ecological studies, yet ecologists have been slow … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…For instance, in thermal ecology, 3D printed lizard models were used as "more standard, lighter, durable, and inexpensive" alternatives to the traditional copper hollow electroformed models for field studies about their thermal properties (Watson & Francis, 2015). In another study, 3D printed lizards were also found to be more efficient than clay models in studies of predation rate (Behm et al, 2018) (Figure 2A). In functional ecology, key questions often involve studying the impact of specific morphological properties of the organism (or part of it).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…For instance, in thermal ecology, 3D printed lizard models were used as "more standard, lighter, durable, and inexpensive" alternatives to the traditional copper hollow electroformed models for field studies about their thermal properties (Watson & Francis, 2015). In another study, 3D printed lizards were also found to be more efficient than clay models in studies of predation rate (Behm et al, 2018) (Figure 2A). In functional ecology, key questions often involve studying the impact of specific morphological properties of the organism (or part of it).…”
Section: Introductionmentioning
confidence: 89%
“…The technology is mature enough for widespread use for research, education and outreach in multiple fields (Lücking, Sambale, Beutel, & Scheper, 2015;Ambrosi & Pumera, 2016;Patra & Young, 2016). However, the use of 3D printing still remains relatively rare in biology, and ecology and evolutionary biology makes no exception (but see Behm, Waite, Hsieh, & Helmus, 2018;Walker & Humphries, 2019). Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because these decoys can be so easily made, researchers can cheaply create numerous mounts that are almost disposable, minimize pseudoreplication, and enhance reliability in ethological studies (Parker, Greig, Nakagawa, Parra, & Dalisio, 2018). 3D printing is revolutionizing many different disciplines within ecology and evolution (Behm, Waite, Hsieh, & Helmus, 2018;Domingue et al, 2015;Igic et al, 2015;Porter, Adriaens, Hatton, Meyers, & McKittrick, 2015;Qing & Bert, 2018), and in the future, advanced modifications, such as iridescent or UV-matched paint colours, instead of animal skins, could remove the need to use live animals in a range of behavioural tests.…”
Section: Seasonal Trade-offs Between Aggression and Parental Care Havementioning
confidence: 99%